Marketing Management department announced that Alfredo Panizales and Milette Zamora, College of Business and Economics faculty joined the prestigious ranks of Certified Professional Marketers (CPMs} - Panizales, Alfredo (Animo Repository, 2001)
Dr. Jaime Ong, Chairperson of the Marketing Management Department announced that Alfredo Panizales and Milette Zamora, College of Business and Economics faculty joined the prestigious ranks of Certified Professional Marketers (CPMs) in Asia-Pacific. As of May 31, 3 out of 8 CPMs in the Philippines were from DLSU-Manila. The first to become one was Dr. Leonardo Garcia, Jr.